Association of Air Pollution and Physical Activity With Brain Volumes. (25th January 2022) - Furlong, Melissa A.; Alexander, Gene E.; Klimentidis, Yann C.; Raichlen, David A.
Abstract : Background and Objectives: In high-pollution areas, physical activity may have a paradoxical effect on brain health by increasing particulate deposition in the lungs. We examined whether physical activity modifies associations of air pollution (AP) with brain volumes in an epidemiologic framework. Methods: The UK Biobank enrolled >500, 000 adult participants from 2006 to 2010. Wrist accelerometers, multimodal MRI with T1 images and T2 fluid-attenuated inversion recovery data, and land use regression were used to estimate vigorous physical activity (VigPA), structural brain volumes, and AP, respectively, in subsets of the full sample. We evaluated associations among AP interquartile ranges, VigPA, and brain structure volumes and assessed interactions between AP and VigPA. Results: Eight thousand six hundred participants were included, with an average age of 55.55 (SD 7.46) years. After correction for multiple testing, in overall models, VigPA was positively associated with gray matter volume (GMV) and negatively associated with white matter hyperintensity volume (WMHV), while NO2, PM2.5absorbance, and PM2.5 were negatively associated with GMV. NO2 and PM2.5absorbance interacted with VigPA on WMHV (false discovery rate–corrected interaction p = 0.037). Associations between these air pollutants and WMHVs were stronger among participants with high VigPA. Similarly, VigPA was negatively associated with WMHV for those in areas of low NO2 and PM2.5absorbance but was null among those living in areas of high NO2 and PM2.5absorbance. Discussion: Physical activity is associated with beneficial brain outcomes, while AP is associated with detrimental brain outcomes. VigPA may exacerbate associations of AP with white matter hyperintensity lesions, and AP may attenuate the beneficial associations of physical activity with these lesions.